Desain Primer untuk Deteksi Gen Diphtheria Toxin Repressor (dtxR) sebagai Biomarker Bakteri Corynebacterium diphtheriae Menggunakan In Silico PCR - Hilari Rio Rosa Nastiti; Rachmad Bayu Kuncara (Poltekkes Kemenkes Semarang, 2023)
Corynebacterium diphtheriae is the bacteria that causes diphtheria. The virulence factor of C. diphtheriae comes from the bacteria's ability to produce bacterial toxins. Toxin production is regulated by a set of genes called tox/dtx genes and is regulated by the dtxR gene. The aim of this study was to design primers used to evaluate the dtxR gene using bacterial DNA sequences. This research is experimental research with a literature study approach using the In silico Polymerase Chain Reaction (PCR), NCBI (National Center for Biotechnology Information), Primer3Plus, and Oligo Calculator applications. The sample obtained from genbank NCBI was C. diphtheriae dtxR gene M80337.1. In silico PCR examination was carried out using newly designed primers from Primer3Plus with 50 genomic DNA of Corynebacterium spp. taken from the In silico PCR database. The dtxR primer pair: '5-ACAGTTAGCCAAACCGTTGC-3' and 5'-TGCGTTCAACTTCGTCACTC-3' can produce a single DNA amplicon measuring 226 bp specifically for C. diphtheria types and no amplicon bands were generated from other Corynebacterium genomes. Based on the study results, this pair of specific primers can be used for in vitro PCR testing and can be used to develop rapid detection of diphtheria.